2017
DOI: 10.1186/s12877-017-0534-0
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative goal setting with elderly patients with chronic disease or multimorbidity: a systematic review

Abstract: BackgroundIt is challenging to use shared decision-making with patients who have a chronic health condition or, especially, multimorbidity. A patient-goal-oriented approach can thus be beneficial. This study aims to identify and evaluate studies on the effects of interventions that support collaborative goal setting or health priority setting compared to usual care for elderly people with a chronic health condition or multimorbidity.MethodsThis systematic review was based on EPOC, PRISMA and MOOSE guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 38 publications
(80 reference statements)
2
94
0
Order By: Relevance
“…Little has been published regarding the extent to which frail older people are involved in care planning. A recent systematic review of collaborative goal setting with older patients with chronic disease found only eight relevant articles on the subject and reported nothing about the level of participant involvement in interventions [17]. However, patient activation (including self-efficacy) has parallels with involvement and a large prospective cohort study found that older people in the UK vary in their levels of activation, with lower levels among depressed, older, retired people with poor health literacy and those who lack social support [18].…”
Section: Discussionmentioning
confidence: 99%
“…Little has been published regarding the extent to which frail older people are involved in care planning. A recent systematic review of collaborative goal setting with older patients with chronic disease found only eight relevant articles on the subject and reported nothing about the level of participant involvement in interventions [17]. However, patient activation (including self-efficacy) has parallels with involvement and a large prospective cohort study found that older people in the UK vary in their levels of activation, with lower levels among depressed, older, retired people with poor health literacy and those who lack social support [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, engaging older patients with multi-morbidity to actively collaborate with health professionals may be challenging due to their frail health, the changing severity of their diseases, and their complex care needs [2]. Previously, health professionals only to a limited extent have collaborated with patients on what matters to them [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies focusing on goal setting practices conclude that practice nurses have difficulty exploring patients' experiences, translating needs, and problems into goals, and making shared decisions about goals and actions (MacDonald, Rogers, Blakeman, & Bower, 2008; van Dillen et al, 2015). This seems to be especially true for goal setting with elderly patients, as elderly people often suffer from multimorbidity and have multi-dimensional goals, which do not focus only on medical aspects, but also on well-being and functioning (Vermunt, Harmsen, Westert, Rikkert, & Faber, 2017).…”
mentioning
confidence: 99%